1994
DOI: 10.1055/s-2007-1021058
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory Fitness, Physical Activity Patterns and Coronary Risk Factors in Preadolescent Boys

Abstract: The relationships between cardiorespiratory fitness, daily physical activity, and selected coronary artery disease (CAD) risk factors were evaluated in a sample of 91 preadolescent boys. Cardiorespiratory fitness was assessed (VO2max). Physical activity level was assessed using daytime heart rate telemetry. CAD risk factors included total cholesterol, fasting triglycerides, HDL-cholesterol, LDL-cholesterol, fasting blood glucose, systolic and diastolic blood pressures, and body fat content. The mean value of V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…The positive association between _ V O 2peak and HDL-C concentration was consistent with previous studies of young people (Al-Hazzaa et al 1994;Armstrong et al 1991;Macek et al 1989;Sallis et al 1988;Suter and Hawes 1993;Tell and Vellar 1988;Valimaki et al 1980). The association between _ V O 2peak and HDL-C concentration (r=0.41) was similar to previous studies of welltrained athletes as well.…”
Section: _ V O 2peak and Blood Lipidssupporting
confidence: 92%
“…The positive association between _ V O 2peak and HDL-C concentration was consistent with previous studies of young people (Al-Hazzaa et al 1994;Armstrong et al 1991;Macek et al 1989;Sallis et al 1988;Suter and Hawes 1993;Tell and Vellar 1988;Valimaki et al 1980). The association between _ V O 2peak and HDL-C concentration (r=0.41) was similar to previous studies of welltrained athletes as well.…”
Section: _ V O 2peak and Blood Lipidssupporting
confidence: 92%
“…Alpert and Wilmore (1994) concluded that aerobic training had only a weak relationship with blood pressure within the normal range, but that such training consistently reduced both systolic and diastolic blood pressure in hypertensive adolescents. Riddoch (1998) reviewed more recent studies and reported that, for lipids and lipoproteins, six studies (Al-Hazzaa et al, 1994;de Visser et al, 1994;Dwyer and Gibbons, 1994;Harrell et al, 1996;Rowland et al, 1996;Webber et al, 1996) showed no association with measures of activity, whereas another six (Suter and Hawes, 1993;Bistritzer et al, 1995;Craig et al, 1996;Gutin et al, 1996;Twisk et al, 1996;Boreham et al, 1997) showed a limited association. For blood pressure, one study (de Visser et al, 1994) reported no association, while seven (Jenner et al, 1992;Al-Hazzaa et al, 1994;Anderson, 1994;Dwyer and Gibbons, 1994;Harrell et al, 1996;Webber et al, 1996;Boreham et al, 1997) reported a bene® cial association.…”
Section: Activity and Current Health Statusmentioning
confidence: 95%
“…In other words, the obese are the unfit, therefore the above findings represent a common phenomena. This is a good point, but when one examines the association between aerobic fitness and fatness the correlation generally ranges from 0.40 to 0.60 (26)(27)(28)(29). Using a correlation of 0.50, this means that the shared variance is only 25%.…”
Section: Mets Scorementioning
confidence: 99%